Possibility of Project Management in the Activities of Non-profit Organizations - KHORIN, Alexander N.; BROVKIN, Alexander V.; POTANINA, Yulia M. (Journal of Advanced Research in Law and Economics; Vol 9 No 4 (2018): JARLE Volume IX Issue 4(34) Summer 2018DO - 10.14505//jarle.v9.4(34).15, 2018)
Modern organizations function in a constantly changing external environment, due to social and scientific progress, there is also the complexity of their internal environment. The result is a high variability of conditions and factors that determine the effectiveness of management. As a result, exacerbated the contradiction between the desire of the organization to maximize typing business processes of their activities (to reduce costs and reduce risks) and the variable nature of the business environment, continuous adaptation is necessary to ensure competitiveness and, eventually, the viability of the organization. Considered the contradiction is evident in the number of private - in contradiction between the standardization of the product and the individual nature of consumer demands, between routine and project components activities organization, etc., Thus, an urgent task for modern research in the field of management theory is the search for balance between standard and unique elements in the work of the organizations. Note that although the practical need to eliminate this contradiction has led to the development of a number of management tools designed to mitigate it, today the problem of the existence of this contradiction has not received proper reflection in the scientific literature. As a result, not only lack understanding of the organizational and economic nature of this contradiction, but the scientifically-methodical device for its elimination. Consider the situation unacceptable from a scientific (without proper consideration remains an important aspect of organization management), or practical (lack of tools eliminate the conflict reduces the effectiveness of both individual enterprises and the economy as a whole) points of view. Particularly acute this contradiction is manifested in the relationship of organizations with major business partners, cooperation with whom has a low level of standardization of business processes because of the complexity and specificity of jointly implemented projects. This places high demands on the quality of managerial decisions taken in the process of business interaction for justification, which requires the development of special methods and algorithms. The result of the phenomena is the decline in the quality of the management decisions due to the fact that organizations are forced to act not proactive, and reactive, developing individual situational tools for each individual project and group business processes, as a result, the risks. All of the above determines the relevance and significance of the chosen research topic.